Conference on Electrical Insulation and Dielectric Phenomena, October 23-26, 1994, Arlington Marriott Hotel, Arlington, Texas - Conference on Electrical Insulation and Dielectric Phenomena (1994 : Arlington, Texas); Institute of Electrical and Electronics Engineers. Dielectrics and Electrical Insulation Society (Piscataway, NJ : IEEE, 1994)
15